Pengembangan Media Oper Tembak Dalam Pembelajaran Permainan Sepakbola Untuk Siswa Kelas V Sekolah Dasar - Isna Nafida; Martin Sudarmono; Sulaiman; Bhayu Billiandri (Universitas Negeri Semarang, 2024)
The background of this study is the lack of enthusiasm of female students towards soccer learning. The lack of supporting facilities and infrastructure is a major factor in learning and the lack of teacher creativity in innovating learning media. The problem in this study is